Cultural Values Analysis in English Textbook ‘Bahasa Inggris’ - Auliana Rahmah; Usman Kasim; Siti Sarah Fitriani (Universitas Syiah Kuala, 2018)
This research is aimed at investigating and describe the cultural values of English Textbook ‘Bahasa Inggris’ published by Kemendikbud by analyzing texts and visual images material based on seven elements of culture proposed by Brown (2001). To analyze the data, the researcher used descriptive qualitative analysis. The data of the research were collected from texts and visual images in the English textbook for senior high school entitled ‘Bahasa Inggris’.To reveal what cultural values are represented in the textbook, the cultural elements are categorized into Social Organization, Custom and Tradition, Language, Religion, Art and Literature, Form of Government, and Economic System. The result obtained was the content of Indonesian culture that accommodating Indonesian students. Furthermore the most frequent element appear in eleven texts and eight visual images being analyzed is Custom and Tradition which found nine times, continued by Art and Literature found seven times, Economic System found six times, Language found three times, as well as Social Organization and Form of Government. The least frequent element appears is Religion; twice. Finding that only thirty three times of the placement of culture elements appeared in the two books, realizing that improvement of cultural content in English textbooks for Senior High School is needed. On the basis of this findings the students, teachers, and author of the book are recommended to pay more attention on adding cultural content in order to have communicative competence of culture.